Barriers to Tuberculosis Case Detection in Private Clinics in Indonesia : A Thematic Analysis - Ritonga, Imelda Liana; Handiyani, Hanny; Nursasi, Astuti Yuni; Eryando, Tris (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2025)
In Indonesia, private clinics have emerged as an alternative healthcare option, even for individuals enrolled in the National Health Insurance program. According to the National Tuberculosis Program, these clinics are also responsible for detecting tuberculosis (TB). However, the ability of these clinics to manage TB patients has not been extensively studied. This study explores the factors that facilitate or hinder healthcare workers (HCWs) at these clinics from detecting TB early on. A qualitative descriptive-interpretative approach was employed. Thirteen HCWs from three clinics, one HCW from a district public healthcare center, and a local TB program supervisor (Wasor TB—deputy supervisor of the Tuberculosis Program) were selected via purposive sampling, resulting in a total of 15 participants. Data were collected through in-depth interviews conducted from April to July 2023 and analyzed using thematic analysis. Three main themes with eight sub-themes emerged: (1) inadequate support from clinic managers for TB services, (2) substandard early TB detection competency among clinical staff, and (3) insufficient support from the external TB network for clinics’ early detection efforts. Improving TB services in private clinics, especially early detection, is essential to achieving the Indonesian government’s goal of eliminating TB by 2030. This can be achieved by reassessing roles and establishing effective collaborative partnerships between clinic leaders and staff and the external TB network.